Preserving the endothelium in saphenous vein graft with both conventional and no-touch preparation - Saito, Toshiro (J Cardiothorac Surg, 2020)
BACKGROUND: Despite the inferior patency compared to arterial grafts, a saphenous vein graft (SVG) is widely used for coronary artery bypass grafting (CABG). A lower atherosclerosis rate and higher patency have been reported for SVG obtained via the no-touch technique (NT) than via conventional preparation (CV). Although CV-mediated endothelial dysfunction is implied, the precise mechanism underlying the higher patency with NT is poorly understood. METHODS: Human residual SVGs during CABG and SVG sections after autopsy were analyzed. The endothelial surface was observed using scanning electron microscopy (SEM) and blindly compared between CV and NT. The endothelial integrity was also analyzed with immunohistochemistry. RESULTS: Unexpectedly, the hyperfine structure on SEM was comparable between CV and NT before grafting, and microvillus, a characteristic of endothelium, was indistinguishable between them. Von Willebrand Factor, an endothelial marker, was equally detected throughout the vascular wall in both groups from residual and postmortem sections. CONCLUSIONS: The morphological integrity of the endothelium was successfully preserved in SVG with CV, even at an ultrastructural level. Although its functionality remains to be addressed, other factors than the endothelium may be involved in the high patency obtained by NT. The present findings suggest that the characteristics of NT and surgical methodology should be reconsidered.